Exploring the relationship between sleep hygiene recommendations and outcomes in sleep, fatigue, and cognitive performance among student-athletes - Varesco, G.; Germain, M.; Szocs, S.; Martin, A.; Toussaint, P.-M.; Simonelli, G. (The Journal of Strength and Conditioning Research, 2026)
Student-athletes often neglect sleep because of academic and training demands, highlighting the value of interventions targeting poor sleep habits. However, sleep hygiene research remains limited to individualized approaches, limiting reproducibility and posing challenges for implementation in large groups, such as collegiate sports teams. In this 4-week study, we assessed the sleep health of an elite collegiate Canadian football team through questionnaires (week 1). Players with poor sleep habits (Pittsburgh Sleep Quality Index > 5; 24 out of 64) participated in a 2-week sleep hygiene intervention. After a familiarization session (week 2), they completed 2 weeks of sleep assessment (actigraphy, sleep diary) and a post-training test, including a fatigue 10-cm visual analog scale, psychomotor vigilance task (PVT), and paced visual serial addition test (PVSAT). Subjects were unaware to be selected based on their poor sleep habits. After week 3, athletes received feedback on poor sleep habits and standardized written, evidence-based sleep hygiene recommendations. They were asked to comply with these recommendations before repeating experimental procedures at the end of week 4. Improvements were observed only in perceived total sleep time (sleep duration; 7:43 ± 1:29 vs. 8:03 ± 1:34 h:mm, p = 0.045) and PVSAT performance (1.44 ± 1.8 vs. 1.36 ± 1.63 seconds, p = 0.004), while PVT speed decreased (3.6 ± 0.4 vs. 3.5 ± 0.4 Hz, p = 0.043). Objective sleep duration (6:53 ± 1:19 vs. 7:04 ± 1:19 h:mm, p = 0.21), fatigue (6 ± 2.1 vs. 5.8 ± 2.1 AU, p = 0.55), and other outcomes remained unchanged (p > 0.37). These results indicate that unsupervised and standardized sleep hygiene recommendations were not associated with changes in sleep habits, with changes in cognitive performance and fatigue level that could not be reconducted to better sleep.